Left Bundle Branch Pacing in a Patient With Dextroposed Heart: A Case Report - Dilip Kumar; Amit Malviya; Rabin Chakraborty; Ashesh Halder; Subhro Sekhar Chakraborty; Anand Kumar Pandey; Pinak Pani Das; Rinchin Dorjee Meegeji (Clinical Case Reports)
ABSTRACT The Right Ventricular (RV) apex has been the standard site for pacing in symptomatic bradyarrhythmias, but chronic RV pacing can cause adverse effects such as atrial arrhythmias and left ventricular dysfunction. Physiological pacing, including His bundle and left bundle pacing, offers alternatives with fewer complications. We present a 66‐year‐old male with a dextroposed heart and fibrotic right lung requiring left bundle branch pacing due to a high RV pacing burden. The procedure involved modified lead placement and a medial subclavian vein puncture, successfully achieving good electrical parameters and post‐procedural device function, highlighting left bundle branch pacing's feasibility in complex anatomical conditions.